The Quranic Response To The Childfree Phenomenon - Nabillah, Adinda Syofiyatun (International Journal of Islamicate Social Studies, 2024)
This article aims to understand deeply how the Qur'an sees the phenomenon of childfree. This qualitative research uses a literature study data collection method from various sources or documents in the form of books, tafsir books or journals. In the verse study, the conceptual maudu'i method is used, which is a method of collecting verses that discuss a topic without the need for specific terms or terms but through a concept on the theme being studied. The findings in this article show that in the Qur'an there is no prohibition on a married couple's decision not to have children. This is because in the Qur'an there are also verses that explain that children can be a test or trial for both parents, so that they have the potential to bring bad things in the future. However, the presence of children in a marriage relationship is basically an innate consequence of marriage. Other verses state the virtues of having children and prayers for good offspring. The presence of children is one of the factors for the realisation of mercy in a marriage. Through several interpretations, it can be interpreted that children can mediate the harmony and happiness of a married couple, as the position of a child who can be Qurrata A'yun for both parents